From a North Cornish pulpit: the sermon notes of Cyril Leslie-Jones, 1911 - 1919. (1st May 2011) - Howlett, Jonathan
The purpose of this article is to put into the public and academic domains the sets of handwritten sermon notes composed by a former vicar of Stratton, near Bude in North Cornwall, the Revd Cyril Leslie-Jones, beginning with his induction in 1911 and ending on the first Sunday after Easter in 1919. This article begins with a brief biographical sketch of the life and work of the Revd Cyril Leslie-Jones. There follows a discussion of each set of his sermon notes, making comment in passing on the personal, Cornish, and wider contexts as appropriate. Finally, in two separate appendices, are the full transcriptions of all ten sets of notes, together with the transcript of an article published posthumously in May 1932 in Home Words, which is the nearest thing to any sort of last words or testament that we have from him.